2019
DOI: 10.3390/rs11121462
|View full text |Cite
|
Sign up to set email alerts
|

Relating X-band SAR Backscattering to Leaf Area Index of Rice in Different Phenological Phases

Abstract: The objective of this study is to provide complete information on the dynamic relationship between X-band (3.11 cm) backscattering intensity (σ • ) and rice crop's leaf area index (LAI) at all growth phases. Though the relationship between X-band σ • and LAI has been previously explored, details on the relationship at the reproductive phase remain unstudied. LAI at the reproductive phase is important particularly at the heading stage where LAI reaches its maximum as it is closely related to grain yield, and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…These results were consistent with those from Jiao et al, 2009, andHosseini et al, 2015, demonstrating that the WCM could estimate LAI over a broader range (LAI of 0.07-3.57 m 2 m −2 for soybeans; 0.04-4.79 m 2 m −2 for corn) [11,21]. More recently, co-polarized X-Band data have also been used to estimate LAI over a study region in the Philippines [19]. They exploited X-HH to estimate LAI of rice during vegetative and reproductive growth stages, with a correlation coefficient of 0.71 reported.…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…These results were consistent with those from Jiao et al, 2009, andHosseini et al, 2015, demonstrating that the WCM could estimate LAI over a broader range (LAI of 0.07-3.57 m 2 m −2 for soybeans; 0.04-4.79 m 2 m −2 for corn) [11,21]. More recently, co-polarized X-Band data have also been used to estimate LAI over a study region in the Philippines [19]. They exploited X-HH to estimate LAI of rice during vegetative and reproductive growth stages, with a correlation coefficient of 0.71 reported.…”
Section: Introductionsupporting
confidence: 88%
“…Based on these criteria, data from three sites (Canada, Germany and Poland) were used for calibration and validation. For each crop type and LAI range, half of the in situ measurements were randomly selected for calibration data, a larger percentage than that used in the previous studies [17,19]. The remainder of the sample points were reserved for independent validation.…”
Section: Selection Of Calibration and Validation Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that the appearance of panicles can not only change the light distribution in a crop canopy, but also considerably affect canopy spectral reflectance [25][26][27][28]. Inoue et al [29] and Asilo et al [30] also reported that panicles influence the relationship between X-band and LAI in rice. Therefore, the influence of panicles on canopy structure is a key factor that affects LAI estimation accuracy during the late growth stages of crops.…”
Section: Introductionmentioning
confidence: 99%
“…Bindlish and Barros, 2001). The vegetation backscatter from (agricultural) canopies has been investigated to gain insights on the phenology (Bakar et al, 1997;Vreugdenhil et al, 2018;Asilo et al, 2019), presence of water stress (McNairn et al, 2002;van Emmerik et al, 2017), and productivity (Li et al, 2003;Setiyono et al, 2019). Vegetation water content (VWC) has been estimated from the vegetation backscatter (Notarnicola and Posa, 2007;Srivastava et al, 2015) and radar vegetation index (RVI, Kim and van Zyl, 2004;Kim et al, 2011Kim et al, , 2013Huang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%